Studying the Types, Bases and Features of Sale from the Perspective of Islamic Jurists - Jafarzadeh, Morad (2021)
Sale is known as one of the most widely used words in Islamic jurisprudence. Islamic jurists have each defined the nature, bases and types of sale as one of the specific and important Islamic contracts. Regarding sale, it should be mentioned that in some definitions, the early Imami jurists considered its nature as the exchange of two properties, while the famous Islamic jurists consider its nature as the demand and acceptance, which makes the object of sale the property of the customer and regards the price as the property of the seller. Another point is that, in the definitions of late and contemporary Imami jurists, there is a kind of semantic alteration in the interpretation of sale. From the view point of Islamic jurists, it seems that the elements of possession and ownership in the sale are concepts with wide conceptual scopes, and this is the superiority and distinction of Imami jurists over other jurists regarding the truth of sale. On the other hand, from the point of view of Islamic jurists, there are different types of sale, the most important of which are strict sale, contractual sale, absent sale, harmful sale, credit sale, general sale, deferred sale, gifted (mohabati) sale, debt sale, Morabahe (a sale based on a fixed price), etc. On the other hand, the bases of sale from the perspective of Islamic jurists are: demand and acceptance, buyer and seller, property sold, and price in the sale contract. Also, the features of sale from the point of view of jurists are: the ownership of the sale, the exchange of the sale, the objectivity of the property, the necessity of the sale contract. The research methodology in this paper is descriptive-analytical using the library method.